2014
DOI: 10.1107/s1399004714017787
|View full text |Cite
|
Sign up to set email alerts
|

Structures of K42N and K42Y sperm whale myoglobins point to an inhibitory role of distal water in peroxidase activity

Abstract: Sperm whale myoglobin (Mb) functions as an oxygen-storage protein, but in the ferric state it possesses a weak peroxidase activity which enables it to carry out H2O2-dependent dehalogenation reactions. Hemoglobin/dehaloperoxidase from Amphitrite ornata (DHP) is a dual-function protein represented by two isoproteins DHP A and DHP B; its peroxidase activity is at least ten times stronger than that of Mb and plays a physiological role. The `DHP A-like' K42Y Mb mutant (K42Y) and the `DHP B-like' K42N mutant (K42N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…The Hill coefficient ( h ) was calculated as 2.9 for F43Y/F138W/P88W Mb, indicating a positive cooperativity. Similar observation was previously reported for K42N Mb ( h = 2.4) in H 2 O 2 -dependent dehalogenation of 2,4,6-trichlorophenol (TCP), which was interpreted by protein dimerization via a dityrosine cross-link during catalysis . This was also confirmed by both ESI-MS spectrometry and SDS-PAGE studies of the protein in reaction with 20 mM H 2 O 2 for 1 min, which showed the formation of a dimeric form (Figure S6).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The Hill coefficient ( h ) was calculated as 2.9 for F43Y/F138W/P88W Mb, indicating a positive cooperativity. Similar observation was previously reported for K42N Mb ( h = 2.4) in H 2 O 2 -dependent dehalogenation of 2,4,6-trichlorophenol (TCP), which was interpreted by protein dimerization via a dityrosine cross-link during catalysis . This was also confirmed by both ESI-MS spectrometry and SDS-PAGE studies of the protein in reaction with 20 mM H 2 O 2 for 1 min, which showed the formation of a dimeric form (Figure S6).…”
supporting
confidence: 87%
“…Similar observation was previously reported for K42N Mb (h = 2.4) in H 2 O 2dependent dehalogenation of 2,4,6-trichlorophenol (TCP), which was interpreted by protein dimerization via a dityrosine cross-link during catalysis. 39 This was also confirmed by both ESI-MS spectrometry and SDS-PAGE studies of the protein in reaction with 20 mM H 2 O 2 for 1 min, which showed the formation of a dimeric form (Figure S6). Note that some oxidations (+16/32 Da) of the protein were observed in the mass spectrum, as reported for native peroxidases such as cytochrome c peroxidase (CcP), 40 which indicates a moderate stability for the enzyme under the reaction conditions, as also shown by the Soret band in Figure 2A during catalysis.…”
supporting
confidence: 61%
“…In experimental studies, researchers are actively working on modifying the function of proteins by introducing amino acid mutations. Especially for myoglobin, which is an oxygen carrier, engineered proteins exhibit enzymatic activity such as peroxidase [29][30][31][32][33]. These mutated sites are primarily located in heme-binding pockets (active sites) other than axial ligands.…”
Section: Introductionmentioning
confidence: 99%